High level of serum cholesteryl ester transfer protein in active hepatitis C virus infection - Satoh, Kenichi (World J Hepatol, 2016)
AIM: To determine the significance of cholesteryl ester transfer protein (CETP) in lipoprotein abnormalities in chronic hepatitis C virus (HCV) infection. METHODS: We evaluated the significance of the serum concentration of CETP in 110 Japanese patients with chronic HCV infection. Fifty-five patients had active HCV infection, and HCV eradication had been achieved in 55. The role of CETP in serum lipoprotein abnormalities, specifically, in triglyceride (TG) concentrations in the four major classes of lipoproteins, was investigated using Pearson correlations in conjunction with multiple regression analysis and compared them between those with active HCV infection and those in whom eradication had been achieved. RESULTS: The serum CETP levels of patients with active HCV infection were significantly higher than those of patients in whom HCV eradication was achieved (mean ± SD, 2.84 ± 0.69 μg/mL vs 2.40 ± 1.00 μg/mL, P = 0.008). In multiple regression analysis, HCV infection status (active or eradicated) was an independent factor significantly associated with the serum CETP level. TG concentrations in low-density lipoprotein (mean ± SD, 36.25 ± 15.28 μg/mL vs 28.14 ± 9.94 μg/mL, P = 0.001) and high-density lipoprotein (HDL) (mean ± SD, 25.9 ± 7.34 μg/mL vs 17.17 ± 4.82 μg/mL, P < 0.001) were significantly higher in patients with active HCV infection than in those in whom HCV eradication was achieved. The CETP level was strongly correlated with HDL-TG in patients with active HCV infection (R = 0.557, P < 0.001), whereas CETP was not correlated with HDL-TG in patients in whom HCV eradication was achieved (R = -0.079, P = 0.56). CONCLUSION: Our results indicate that CETP plays a role in abnormalities of lipoprotein metabolism in patients with chronic HCV infection.